الحذف في اللغتين العربية والإنجليزية ودلالته دراسة وصفية تقابلية - أحمد، تلار سالار (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2015)
The current research is considered as an applied research that addresses ellipsis, a linguistic feature used in both languages Arabic and English. The study seeks to investigate this particular by defining its similarities and differences in the two languages using the descriptive approach to describe the language systems. This is followed by the contrastive approach which highlights what researchers have decided regarding ellipsis which is the focus of the current research. The research also discusses semantic ellipsis in both Arabic and English at all linguistic levels to define the similarities and differences between them in order to help non-native learners and curriculum designers The study addresses ellipsis in the Arabic language both in past and present, as well as its terms, types, elements, and significance. This is followed by studying ellipsis in the English language both in past and present too as well as its terms, types, elements and significance. At the end of the study, a contrasting process on ellipsis between the two languages was conducted. The research identifies some important observations: there are some similarities between the two languages in regards to ellipsis and its general purposes. The differences canbe found in the "inflection" and "structuring”. Arabic is shown to be an inflective language in which its words are affected by the factors preceding them, while English is not affected as words are structured and unchangeable. English also differs from Arabic in its sentence order which begins with verb, subject, including subject and predicate, in verb forms and tenses. The last observation is that Arabic has masculine and feminine verb forms, while the verbs in English do not change their forms, because masculine and feminine forms are the same. Finally, the research concludes with some potential difficulties that could face non-native- learners especially during the learning process.